HEALTH EDUCATION BY PEER COUNSELORS INCREASES ADOLESCENT KNOWLEDGE ABOUT HEALTHY LIFESTYLES - Rachmawati, Praba Diyan; Dwi Kurnia, Iqlima; Sufyanti Arief, Yuni; Qur'aniati, Nuzul; Kristiawati, Kristiawati; Krisnana, Ilya; Nastiti, Aria Aulia (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2024)
Introduction: Adolescents have tend to lead an unhealthy lifestyle, such as liking to consume unhealthy food and sedentary behavior. The current phenomenon is an increase in the incidence of obesity and non-communicable diseases in Adolescents that are caused by unhealthy lifestyle. This community service activity aims to optimize the role of peers in providing health education to increase knowledge about healthy lifestyles for Adolescents. Methods: This community service method provided health education to Adolescents by peer counselors. This community service was carried out at Junior High School (SMPN) 62 Surabaya in July to August 2024. Peer counselors provided health information about healthy lifestyles which include healthy eating behavior and physical activity with interactive discussions in small groups. Participants in this community service activity consisted of 5 peer counselors and 20 Adolescents in 8th grade. Each peer counselor provided health education to 4 Adolescents. The activity stages include selecting peer counselors, increasing the knowledge capacity and skills of peer counselors. After receiving training, peer counselors then provide health education to other Adolescents about healthy lifestyles during puberty, then the knowledge of adolescents was evaluated using questionnaire about healthy lifestyles. Results: The results of this community service show an increase in the average value of knowledge about healthy lifestyles in Adolescents after providing health knowledge about diet and physical activity by peer counselors. The average score increased and 65% of students had high knowledge after being given health education, including knowledge about balanced nutrition, healthy food, the importance of breakfast, nutritional status and physical activity. Conclusion: Health education by peer counselors   through peer counselor clinics program has proven to be effective in increasing the knowledge and motivation of adolescents in participating in health education. Peer counselor activities are recommended to become a program for middle schools that regularly maintain adolescent health behavior, through activities providing health education, and monitoring adolescent growth, such as measuring the nutritional status of adolescents periodically.